Mannheim carotid intima-media thickness consensus (2004-2006): an update on behalf of the Advisory Board of the 3rd and 4th Watching the Risk Symposium, 13th and 15th European Stroke Conferences, Mannheim, Germany, 2004, and Brussels, Belgium, 2006 - Touboul, Pierre-Jean; Hennerici, Michael G.; Meairs, S.; Adams, H.; Amarenco, P.; Bornstein, N.; Csiba, L.; Desvarieux, M.; Ebrahim, S.; Fatar, M.; Hernandez Hernandez, R.; Jaff, M.; et al. (Cerebrovascular diseases, 2007)
Intima-media thickness (IMT) is increasingly used as a surrogate end point of vascular outcomes in clinical trials aimed at determining the success of interventions that lower risk factors for atherosclerosis and associated diseases (stroke, myocardial infarction and peripheral artery diseases). The necessity to promote further criteria to distinguish early atherosclerotic plaque formation from thickening of IMT and to standardize IMT measurements is expressed through this updated consensus. Plaque is defined as a focal structure that encroaches into the arterial lumen of at least 0.5 mm or 50% of the surrounding IMT value or demonstrates a thickness >1.5 mm as measured from the media-adventitia interface to the intima-lumen interface. Standard use of IMT measurements is based on physics, technical and disease-related principles as well as agreements on how to perform, interpret and document study results. Harmonization of carotid image acquisition and analysis is needed for the comparison of the IMT results obtained from epidemiological and interventional studies around the world. The consensus concludes that there is no need to 'treat IMT values' nor to monitor IMT values in individual patients apart from exceptions named, which emphasize that inside randomized clinical trials should be performed. Although IMT has been suggested to represent an important risk marker, according to the current evidence it does not fulfill the characteristics of an accepted risk factor. Standardized methods recommended in this consensus statement will foster homogenous data collection and analysis. This will help to improve the power of randomized clinical trials incorporating IMT measurements and to facilitate the merging of large databases for meta-analyses.
Published online: November 14, 2006
Gesehen am 02.05.2022